Toxic consequences and oxidative protein carbonylation from chloropicrin exposure in human corneal epithelial cells. (1st April 2020) - Goswami, Dinesh G; Kant, Rama; Ammar, David A; Agarwal, Chapla; Gomez, Joe; Agarwal, Rajesh; Saba, Laura M; Fritz, Kristofer S; Tewari-Singh, Neera
Graphical abstract: Abstract: Chloropicrin (CP), a warfare agent now majorly used as a soil pesticide, is a strong irritating and lacrimating compound with devastating toxic effects. To elucidate the mechanism of its ocular toxicity, toxic effects of CP (0–100 μM) were studied in primary human corneal epithelial (HCE) cells. CP exposure resulted in reduced HCE cell viability and increased apoptotic cell death with an up-regulation of cleaved caspase-3 and poly ADP ribose polymerase indicating their contribution in CP-induced apoptotic cell death. Following CP exposure, cells exhibited increased expression of heme oxygenase-1, and phosphorylation of H2A.X and p53 as well as 4-hydroxynonenal adduct formation, suggesting oxidative stress, DNA damage and lipid peroxidation. CP also caused increases in mitogen activated protein kinase-c-Jun N-terminal kinase and inflammatory mediator cyclooxygenase-2. Proteomic analysis revealed an increase in the carbonylation of 179 proteins and enrichment of pathways (including proteasome pathway and catabolic process) in HCE cells following CP exposure. CP-induced oxidative stress and lipid peroxidation can enhance protein carbonylation, prompting alterations in corneal epithelial proteins as well as perturbing signaling pathways resulting in toxic effects. Pathways and major processes identified following CP exposure could be lead-hit targets for further biochemical and molecular characterization as well as therapeutic intervention.